LITERATURE REVIEW : EFEKTIVITAS PEMBERIAN JAHE TERHADAP MUAL MUNTAH IBU HAMIL - Laeli Chaerina; Hernayanti Nurmalasari; Lienji Amelia; Della Afrilliani Sutaryo; Trisha Kania Sugandi; Heri Ridwan; Diding Kelana Setiadi (Jurnal Keperawatan Abdurrab, 2024)
Background : Although being pregnant is a wonderful time in a woman's life, the first trimester in particular can present health risks like nausea and vomiting. Depending on the intensity of the symptoms, nausea and vomiting during pregnancy are managed and treated with both pharmaceutical and non-pharmacological therapies. Objective : This study aims to evaluate the effectiveness of ginger administration in addressing nausea and vomiting in pregnant women. Method : Our research is a Systematic Literature Review (SLR) using the PRISMA (Preferred Reporting Items for Systematic Reviews and meta-analyses) technique. A journal search was carried out via Publish or Perish (POP) using the Google Scholar database with a period of 2019-2023, and 2,148 journals were found, with selection based on full text access, Indonesian language, and download availability. Result : Out of the 11 selected studies, the results indicate that ginger in various forms (beverages, candies, powders, infused water) is effective in reducing the intensity of nausea and vomiting in pregnant women during the first trimester. Conclusion : The conclusion was drawn that there was a difference in the average between pregnant women who consumed ginger food and those who did not consume it at all. Many of the results of the research found results that stated that pregnant women felt the effectiveness of ginger food starting from the frequency of nausea and vomiting which was rarely felt until pregnant women who no longer feel nausea and vomiting after diligently consuming ginger food.